Politics and ideology in Canada : elite and public opinion in the transformation of a welfare state - Ornstein, Michael D. (McGill-Queen's University Press, 1999)
"Politics and Ideology in Canada examines a period of crucial historical change in Canada, beginning in the mid-1970s, when the crisis of the Keynesian welfare state precipitated a transition to a new political order based on the progressive "downsizing" of state involvement in the economy and society. Using class and ideology as key concepts, Michael Ornstein and Michael Stevenson examine this transition in terms of the nature of hegemony and hegemonic crisis and the conditions of political order and instability. These concepts guide the interpretation of three large surveys of representative samples of the Canadian public and two unique elite surveys, conducted between 1975 and 1981. The surveys cover an exceptionally broad spectrum of political issues, including social programs, civil and economic rights, economic policy, foreign ownership, labour relations, and language issues and sovereignty."--Jacket